Autologous Endothelial Progenitor Cells Transplantation for Acute Ischemic Stroke: A 4-Year Follow-Up Study. (29th August 2018) - Fang, Jie; Guo, Yang; Tan, Sheng; Li, Zhanhui; Xie, Huifang; Chen, Pingyan; Wang, Kai; He, Zhicong; He, Peng; Ke, Yiquan; Jiang, Xiaodan; Chen, Zhenzhou
Abstract: Transplantation of endothelial progenitor cells (EPCs) is a proven safe and effective method for treatment of cerebral ischemia in animal experiments. However, safety and efficacy need to be determined in clinical trials. We performed a two-center, randomized, placebo-controlled phase I/IIa trial with blinded outcome assessment on 18 patients with acute cerebral infarct within the middle cerebral artery territory, and followed for up to 4 years. Autologous ex vivo expanded EPCs were injected intravenously in the EPC group, and patients who received saline or autologous bone marrow stromal cells served as control groups. Mortality of any cause, adverse events, and new-onset comorbidities were monitored. Changes in neurological deficits were assessed at different time points. We found no toxicity events or infusional or allergic reactions in any treated group. Three patients in the placebo group died during the 4-year follow-up. We found that the EPC group had fewer serious adverse events compared with the placebo-controlled group, although there were no statistical differences in mortality among the three groups. Furthermore, there was no significant difference in neurological or functional improvement observed among the three groups, except for the Scandinavia Stroke Scale score at 3 months between the EPC group and placebo-controlled group. Autologous transplantation of EPCs appears to improve long-term safety in acute cerebral infarct patients, supporting the feasibility of this novel method for treatment of ischemic stroke (ClinicalTrials.gov: NCT01468064). Stem Cells Translational Medicine   2019;8:14–21